ANALISIS KEMAMPUAN PEMECAHAN MASALAH PADA MATERI TEOREMA PHYTAGORAS SISWA KELASVIII SMP NEGERI 12 SIGI: Analysis Of Problem Solving Skills On Pythagorean Theorem Material For Students In Class VIII SMP Negeri 12 Sigi - Widiastuti, Ira; Nurhayadi, Nurhayadi; Idris, Mustamin; Rizal, Muh. (Universitas Tadulako, 2025)
The purpose of this study was to obtain a description of students' problem solving ability on the Pythagorean theorem material of class VIII students of SMP Negeri 12 Sigi. This type of research is qualitative research. The subjects in this study were three students of class VIII SMP Negeri 12 Sigi in the odd semester of the 2023/2024 school year consisting of one student each with high, medium, and low mathematics abilities. Data collection techniques used observation sheets, written tests and interviews. The results of this study indicate that (1) high mathematics ability students can understand the problem, plan the solution, implement the plan, and check back, (2) moderate mathematics ability students can understand the problem, plan the solution, and implement the plan but cannot do a check back, (3) low mathematics ability students are unable to understand the problem, plan the solution, implement the plan, and check back.